2015
DOI: 10.1248/bpb.b14-00709
|View full text |Cite
|
Sign up to set email alerts
|

3β-Angeloyloxy-8β,10β-dihydroxyeremophila-7(11)-en-12,8α-lactone Inhibits Lipopolysaccharide-Induced Nitric Oxide Production in RAW264.7 Cells

Abstract: Farfugium japonicum (L.) KITAM, named "Lian-Peng-Cao" in China, has been traditionally used in Chinese folk medicine to treat sore throat, cold and cough due to its anti-inflammatory properties. In this study, the anti-inflammatory action of 3β-angeloyloxy-8β,10β-dihydroxyeremophila-7(11)-en-12,8α-lactone (FJ1) isolated from Farfugium japonicum and its molecular mechanism in RAW264.7 cells were investigated. 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay showed that FJ1 with or withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…After 4 h of treatment, the cells were incubated with or without LPS (1 µg/mL) for 24 h. The culture mediums were collected and analyzed for IL-6, TNF-α, and PGE 2 production using ELISA kits according to the manufacturer's protocol. 21,22) To determine the total concentration of NO in the culture media, 150 µL of Griess reagent (1% sulfanilamide, 0.1% N-1-naphthylenediamine dihydrochloride and 2.5% phosphoric acid) was mixed with 150 µL of the supernatant and the absorbance at 540 nm was evaluated using a microplate reader. 23) Western Blot Analysis Preparations of whole cell lysates, cytoplasmic and nuclear fractions were carried out according to the previously published procedures.…”
Section: Methodsmentioning
confidence: 99%
“…After 4 h of treatment, the cells were incubated with or without LPS (1 µg/mL) for 24 h. The culture mediums were collected and analyzed for IL-6, TNF-α, and PGE 2 production using ELISA kits according to the manufacturer's protocol. 21,22) To determine the total concentration of NO in the culture media, 150 µL of Griess reagent (1% sulfanilamide, 0.1% N-1-naphthylenediamine dihydrochloride and 2.5% phosphoric acid) was mixed with 150 µL of the supernatant and the absorbance at 540 nm was evaluated using a microplate reader. 23) Western Blot Analysis Preparations of whole cell lysates, cytoplasmic and nuclear fractions were carried out according to the previously published procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Compounds 1 – 7 were evaluated for their ability to inhibit NO production in LPS‐stimulated RAW264.7 cells using the Griess assay (Sun et al ., 2015). Notably, none of the compounds displayed cytotoxicity with murine macrophage RAW264.7 cells using the MTT [3‐(4,5‐dimethylthiazol‐2‐yl)‐2,5‐diphenyl‐2H‐tetrazolium bromide, Sigma] assay (IC 50 > 48 μM; Table S14; Alley et al ., 1988), which suggested that any inhibition of NO production would not be due to cytotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…En la búsqueda de nuevos antiinflamatorios, muchos compuestos derivados de plantas han sido investigados en su actividad antiinflamatoria in vivo y en los mecanismos de acción involucrados, centrando el foco en la inhibición de la producción de mediadores proinflamatorios y en la inhibición de la expresión de enzimas y de la activación de factores de trascripción implicados en las respuestas inflamatorias (Risitano et al, 2014;Chen et al, 2015;Choi et al, 2015;Fang et al, 2015;Hong et al, 2015;Limtrakul et al, 2015;Sun et al, 2015). (Ríos et al, 2009).…”
Section: I3 Búsqueda De Nuevos Fármacos Antiinflamatoriosunclassified